2011
DOI: 10.4038/cmj.v56i1.2895
|View full text |Cite
|
Sign up to set email alerts
|

Perception of pain during episiotomy in a tertiary care centre in Sri Lanka

Abstract: Research letters Episiotomy is used almost routinely in vaginal deliveries in Sri Lanka and the norm is for it to be performed without anaesthesia. This is due to the popular belief that episiotomy could be performed painlessly without anaesthesia if it is performed at the peak of a contraction when the perineum is at full stretch. This practice is also convenient, since nurses and midwives involved in normal deliveries in Sri Lanka are not licensed to administer a local anaesthetic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This audit showed that 21.0% episiotomies were performed without local analgesia. A previous Sri Lankan study has also demonstrated that women suffer from significant pain since a majority of episiotomies were performed without analgesia 1 . Main reason is that nurses and midwives involved in normal deliveries in Sri Lanka are not licensed to administer a local anaesthetic 1 and this needs to be addressed in a practical way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This audit showed that 21.0% episiotomies were performed without local analgesia. A previous Sri Lankan study has also demonstrated that women suffer from significant pain since a majority of episiotomies were performed without analgesia 1 . Main reason is that nurses and midwives involved in normal deliveries in Sri Lanka are not licensed to administer a local anaesthetic 1 and this needs to be addressed in a practical way.…”
Section: Discussionmentioning
confidence: 99%
“…Episiotomy is used almost routinely in vaginal deliveries in Sri Lanka 1 . However, it is indicated in certain situations including the instrumental vaginal deliveries and shoulder dystocia 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the current practice is routine episiotomy in most institutions [7,9], there is no added cost in implementing the intervention. Rather, it is an omission of a procedure already in place.…”
Section: Feasibilitymentioning
confidence: 99%
“…More importantly, recent evidence demonstrates more harm in the procedure than benefit [6]. In Sri Lanka, episiotomy is used almost routinely in vaginal deliveries without anaesthesia [7], despite the national recommendation to avoid routine episiotomy during spontaneous vaginal birth [8]. Many local studies confirm widespread use of routine episiotomy in the local setting.…”
Section: Introductionmentioning
confidence: 99%
“…The current recommendation is that "routine" episiotomy should be abandoned. Limiting the use of episiotomy is strongly recommended to help protect the integrity of the perineum 2 . Until further research is done, episiotomy should be considered only for certain conditions like; assisted vaginal delivery (forceps or vacuum), preterm delivery, breech delivery, foetal compromise or predicted macrosomia.…”
Section: Introductionmentioning
confidence: 99%